A survey on information processing technologies in wireless sensor networks. (25th May 2006) - Yuan, Yong; Yang, Zongkai; Chen, Min; He, Jianhua
Recent advances of wireless sensor network have proposed many challenges on networking and information processing technologies. However, most research work in wireless sensor networks focused on networking protocols with only little work on information processing beyond what is referred to as 'aggregation'. This paper surveys the recent work on the information processing technologies in wireless sensor networks for promoting novel technologies. The three main categories of the technologies explored in this paper are energy aware information processing algorithms design, space time signal processing algorithms and networked information processing algorithms.